DIRECTED MIGRATION AS THE MEANS TO ACHIEVE THE HYBRID WAR GOALS - Danyk, Y.; Semenkova, M. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The need to study the contemporary migration processes inter alia taking into account the feasibility of using them as the means of the domestic and foreign policy, for example to achieve the goals of the hybrid war was substantiated. On the one hand it can be explained by the changing approaches to the realization of political interests, particularly to the waging of war; on the other hand – by the peculiarities of the contemporary migration processes. It was shown that for the migration processes to be used they have to be eligible to external influence, besides they can be influenced in a hidden way or their use can be explained by the acceptable purposes. They must also be effective enough that means their use can help actor to achieve its political goal. The concept of the directed migration was introduced and the ways the directing of migration processes can be executed at the different stages of the migration process were shown as well as the role of the informatization and mass communication. Particularly, the assumption was made that the hybrid conflict in a particular region can be waged just to initiate and stimulate migration in order to destabilize the situation in the region where the migration flows are directed to. Possibilities of using directed migration by a political actor to destabilize the political, socio-economic and ideological spheres of the target country or region from within were also analyzed. Given that, both the country of origin and the host country can be regarded as the target one. The increasing of conflictogenity of the society due to the horizontal inequality transformation between migrants and host community was presented as an example.